Alcoholic Liver Disease Epidemiology in the United States: A Retrospective Analysis of 3 US Databases. (January 2020) - Dang, Katherine; Hirode, Grishma; Singal, Ashwani K.; Sundaram, Vinay; Wong, Robert J.
Abstract : OBJECTIVES: Alcoholic liver disease (ALD) prevalence, particularly the subset with advanced liver disease, is not well defined. Herein, we aim to provide a comprehensive assessment of ALD epidemiology across the spectrum of disease severity and across different settings using 3 unique US databases. METHODS: We performed a retrospective, observational study of US adults with ALD using 2001–2016 National Health and Nutrition Examination Survey (NHANES), 2007–2014 Nationwide Inpatient Sample (NIS), and 2007–2017 United Network for Organ Sharing (UNOS) registry. ALD in the NHANES was defined using clinical laboratory data and self-reported alcohol use, among which fibrosis-4 score of >2.67 defined stage ≥3 fibrosis. Alcoholic cirrhosis (AC) in the NIS was identified using International Classification of Diseases, Ninth Revision codes. ALD in the UNOS was identified using UNOS coding. RESULTS: From 2001–2002 to 2015–2016, the overall weighted ALD prevalence was stable from 8.8% to 8.1% ( P = 0.102), whereas the proportion of ALD with stage ≥3 fibrosis increased from 2.2% (95% CI: 0.4–4.0) to 6.6% (95% CI: 2.0–9.9; P = 0.007) (NHANES). From 2007 to 2014, the number of hospitalizations among patients with AC per 1, 000 increased by 32.8%, and the proportion of hospitalizations among the patients with AC with ≥3 cirrhosis complications increased from 11.6% in 2007 to 25.8% in 2014 ( P trend < 0.0001) (NIS). From 2007 to 2017, the total number of adults with ALD listed for liver transplant increased by 63.4% and the proportion with concurrent hepatocellular carcinoma increased by 178% (UNOS). DISCUSSION: Among these 3 US databases, consistent observations of increasing ALD severity emphasize the urgent need for greater awareness about the consequences of unhealthy alcohol use and interventions aimed specifically at addressing alcohol use disorders.